Effect of social media on Academic Learning Achievement of the University Students: A case study of UOS Bhakkar Campus Students - Muhammad Asim; Mohsin Raza; Ayesha Abid; Muhammad Ahsan; Mussarat Hussain (Journal of Management Practices, Humanities and Social Sciences, 2021)
The study aims to inspect the effect of social media, and academic learning achievement of students. The main objectives of the current study were to analyze the association between the use of social media and students' academic learning achievement and assess the level of academic performance among students concerning the intensive use of social media. A quantitative research design was used, and data has been collected from 120 students through a questionnaire using a simple random sampling technique. A Paired sample t-Test has been applied in this research to test the hypothesis. This study showed that social media positively influences the academic learning achievement of UOS Bhakkar campus students. However, it was concluded that the significant value sig= (.000) was less than .05, which was an actual measure for accepting or rejecting the hypothesis, so the null hypothesis was rejected, and the main hypothesis was accepted. There is a significant association between the use of Social Media and students' academic learning achievement. The study will support the government and university regarding making facilities available, such as the Internet, etc. It will also draw students' courtesy to the need for responsible use of social media in their academic work.